On the size of fiscal multipliers: A counterfactual analysis - Jan Kuckuck; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2013)
The Structural Vector Auto-regression (SVAR) approach to estimating fiscal multipliers, following the seminal paper by Blanchard and Perotti (2002), has been widely applied in the literature. In our pa-per we discuss the interpretation of these estimates and suggest that they are more useful for fore-casting purposes than for policy advice. Our key point is that policy instruments often react to each other. We analyze a data set from the US and document that these interactions are economically and statistically significant. Increases in spending have been financed by subsequent increases in taxes. Increases in taxes have been complemented by additional spending cuts in subsequent quarters. In a counterfactual analysis we report fiscal multipliers that abstract from these dynamic responses of policy instruments to each other.
Keywords: E62; H20; H50; 330; Fiscal policy; government spending; net revenues; structural vector autoregression